Company Employee Empowerment Model for Equitable Development - Andini Fauzyah Salsabilah; Syafriwaldi Syafriwaldi (Indev: Literasi Media Dakwah dan Pengembangan Masyarakat, 2023)
The main problem in this study is the employee empowerment model carried out by CV. Kempan Sumatra Resource for company employees. The aim is to find out and analyze the forms, stages and constraints in the empowerment model for company employees at CV. Kempan Sumatra Resources. The type of research used is descriptive research with a qualitative approach. The results of this study found that there were two forms of training carried out, namely training provided by related agencies and training outside the region. The stages carried out by the CV. Kempan Sumatra Resource went through several stages such as preparing materials, media, resource persons and program implementation. Constraints found by the CV. Kempan Sumatra Resource in implementing the empowerment model for employees, namely in the form of limited human resources, non-strategic locations and facilities to support empowerment.